Patterns of co-occurrence and body size in dragonflies and damselflies (Insecta: Odonata) in preserved and altered Amazonian streams - Oliveira-Junior, José Max B. (2021)
Interspecific interactions, such as competition, are among the key factors that determine the distribution, abundance and diversity of organisms in natural communities of aquatic ecosystems. However, a marked reduction in the environmental integrity of streams may lead to modifications of the natural dynamics of these communities, including co-occurrence patterns and body size. In the Amazon, the replacement of forests by production systems is one of the leading causes of alterations to riverine ecosystem. The insects of the order Odonata (dragonflies and damselflies) are predators known to compete for environmental resources but are also sensitive to environmental changes such as those caused by shifts in land use. In this scenario, the present study evaluated species co-occurrence and body size patterns in adult odonates found at preserved and altered Amazonian streams, to determine whether there are morphological differences among the species that enable their coexistence. During the study, 98 streams in the eastern Amazon region were sampled, and a habitat integrity index (HII) was used to evaluate the integrity of each stream (based on variables such as the condition of the riparian vegetation and channel, and land use). Ten male individuals were selected from each species, and nine morphometric measurements were taken from each individual. A total of 3588 specimens were collected and distributed in nine families, 49 genera and 134 species. We found a non-random pattern of co-occurrence in the species of the odonate suborder Zygoptera and a random pattern in the suborder Anisoptera, in both preserved and altered streams. We found morphological divergence between pairs of zygopteran species, in the whole sample and both categories of stream integrity separately. No such morphological divergence was found in the pairs of anisopteran species. The distribution patterns of odonate species are limited by specific environmental processes, especially in preserved environments and in specialists, such as most zygopterans. Zygopteran species have more specific microhabitat requirements, which could explain this pattern, whereas anisopterans prefer open environments, which usually have a greater supply of resources, although there tends to be less microhabitat heterogeneity, which leads to reduced competition. Given this, future studies should use limiting similarity (e.g. morphological attributes) in addition to environmental and spatial factors to better understand the factors structuring these communities. Among these mechanisms, the effects of common ancestry (phylogenetic inertia) and biogeography are important factors that should also be considered in future studies.